Efficacy and Safety of Defibrotide for the Treatment of Hepatic Veno-Occlusive Disease after Hematopoietic Stem Cell Transplantation: A Systematic Review and Meta-Analysis - Yang, Liping; Qi, Jiaqian; Pan, Tingting; You, Tao; Ruan, Changgeng; Han, Yue (Seminars in Thrombosis and Hemostasis, 2019)
Defibrotide has been approved in several geographic jurisdictions for the treatment of hepatic veno-occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) for years. However, available data on efficacy and safety for its use in VOD are contrasting. We performed a meta-analysis to evaluate the efficacy and safety of defibrotide in the treatment of hepatic VOD/SOS post-hematopoietic stem cell transplantation (HSCT). PubMed and Embase were searched for studies regarding the efficacy and safety of defibrotide in VOD patients. Survival rate at day + 100 post-HSCT (D + 100 SR), as well as the prognosis, comprising complete response (CR), adverse events including ≥1 adverse event (≥1 AE), hemorrhage, and serious adverse events (SAEs), were pooled using a random effect model. Sixteen studies involving 3,002 participants were included. Pooled estimates for overall D + 100 SR as well as rate of CR, ≥1 AE, hemorrhage, SAEs in VOD patients post-HSCT were 58% (95% CI: 54–62%), 57% (95% CI: 45–68%), 65% (95% CI: 54–75%), 16% (95% CI: 5–27%), 53% (95% CI: 51–55%), respectively, and were 44% (95% CI: 39–48%), 39% (95% CI: 28–50%), 88% (95% CI: 71–100%), 42% (95% CI: 30–55%), 58% (95% CI: 52–64%), respectively, in severe VOD (sVOD) patients. Hemorrhage and hypotension were the most common AEs. Current evidence suggests that defibrotide improves the D + 100 SR and CR in VOD/sVOD patients following HSCT. However, the results of this review/meta-analysis were mainly based on data from observational studies, potentially subject to selection bias. Consequently, higher quality randomized control trials and larger prospective cohort studies are warranted.
Keywords: hepatic veno-occlusive disease; sinusoidal obstruction syndrome; defibrotide; hematopoietic stem cell transplantation.